Chikungunya virus infection results in higher and persistent viral replication in aged rhesus macaques due to defects in anti-viral immunity. - Ilhem Messaoudi; Jennifer Vomaske; Thomas Totonchy; Craig N Kreklywich; Kristen Haberthur; Laura Springgay; James D Brien; Michael S Diamond; Victor R Defilippis; Daniel N Streblow (Public Library of Science (PLoS), 2013)
Chikungunya virus (CHIKV) is a re-emerging mosquito-borne Alphavirus that causes a clinical disease involving fever, myalgia, nausea and rash. The distinguishing feature of CHIKV infection is the severe debilitating poly-arthralgia that may persist for several months after viral clearance. Since its re-emergence in 2004, CHIKV has spread from the Indian Ocean region to new locations including metropolitan Europe, Japan, and even the United States. The risk of importing CHIKV to new areas of the world is increasing due to high levels of viremia in infected individuals as well as the recent adaptation of the virus to the mosquito species Aedes albopictus. CHIKV re-emergence is also associated with new clinical complications including severe morbidity and, for the first time, mortality. In this study, we characterized disease progression and host immune responses in adult and aged Rhesus macaques infected with either the recent CHIKV outbreak strain La Reunion (LR) or the West African strain 37997. Our results indicate that following intravenous infection and regardless of the virus used, Rhesus macaques become viremic between days 1-5 post infection. While adult animals are able to control viral infection, aged animals show persistent virus in the spleen. Virus-specific T cell responses in the aged animals were reduced compared to adult animals and the B cell responses were also delayed and reduced in aged animals. Interestingly, regardless of age, T cell and antibody responses were more robust in animals infected with LR compared to 37997 CHIKV strain. Taken together these data suggest that the reduced immune responses in the aged animals promotes long-term virus persistence in CHIKV-LR infected Rhesus monkeys.